The Impact of Medical Comorbidities on Primary Total Knee Arthroplasty Reimbursements - Sabeh, Karim G.; Rosas, Samuel; Buller, Leonard T.; Freiberg, Andrew A.; Emory, Cynthia L.; Roche, Martin W. (The Journal of Knee Surgery, 2019)
Medical comorbidities have been shown to cause an increase in peri-and postoperative complications following total knee arthroplasty (TKA). However, the increase in cost associated with these complications has yet to be determined. Factors that influence cost have been of great interest particularly after the initiation of bundled payment initiatives. In this study, we present and quantify the influence of common medical comorbidities on the cost of care in patients undergoing primary TKA. A retrospective level of evidence III study was performed using the PearlDiver supercomputer to identify patients who underwent primary TKA between 2007 and 2015. Patients were stratified by medical comorbidities and compared using analysis of variance for reimbursements for the day of surgery and over 90 days postoperatively. A cohort of 137,073 US patients was identified as having undergone primary TKA between 2007 and 2015. The mean entire episode-of-care reimbursement was $23,701 (range: $21,294–26,299; standard deviation [SD] $2,611). The highest reimbursements were seen in patients with chronic obstructive pulmonary disease (mean $26,299; SD $3,030), hepatitis C (mean $25,662; SD $2,766), morbid obesity (mean $25,450; SD $2,154), chronic kidney disease (mean $25,131, $3,361), and cirrhosis (mean $24,890; SD $2,547). Medical comorbidities significantly impact reimbursements, and therefore cost, after primary TKA. Comprehensive preoperative optimization for patients with medical comorbidities undergoing TKA is highly recommended and may reduce perioperative complications, improve patient outcome, and ultimately reduce cost.
Keywords: total knee arthroplasty; replacement; medical comorbidities; cost; reimbursement; bundled payment